2008
DOI: 10.1007/s00276-008-0435-1
|View full text |Cite|
|
Sign up to set email alerts
|

Surgical anatomy of the presacral area

Abstract: This study showed that there was close distance between the sacral midline and the structures anterior to it. The close relationships, as well as the potential for anatomical variations, require the use of sacral and presacral imaging before presacral approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
0
16
0
1
Order By: Relevance
“…However, (13), (14), (15), (16) found that In fourth age group(20-40 years) of European individuals the mean Coccygeal curved length in male is 3.9± 0.7 cm , while in female is 3.6 ± 0.7 cm. This difference is significant.…”
Section: Measurements Of Coccyxmentioning
confidence: 97%
“…However, (13), (14), (15), (16) found that In fourth age group(20-40 years) of European individuals the mean Coccygeal curved length in male is 3.9± 0.7 cm , while in female is 3.6 ± 0.7 cm. This difference is significant.…”
Section: Measurements Of Coccyxmentioning
confidence: 97%
“…The coccygeal region is principally supplied from the median and lateral sacral arteries, which run in the presacral space. The median sacral artery arises immediately above the posterior aspect of the aortic bifurcation, descends posterior to the sacral venous plexus usually to one or other side of the midline, and anastomoses with the lateral sacral arteries which send branches through the anterior sacral foramina (Esses et al,1991; Tribus and Belanger,2001; Guvencer et al,2009). The median sacral artery is about 2.3 mm wide at the coccyx (Tribus and Belanger,2001; Guvencer et al,2009).…”
Section: Resultsmentioning
confidence: 99%
“…The median sacral artery arises immediately above the posterior aspect of the aortic bifurcation, descends posterior to the sacral venous plexus usually to one or other side of the midline, and anastomoses with the lateral sacral arteries which send branches through the anterior sacral foramina (Esses et al,1991; Tribus and Belanger,2001; Guvencer et al,2009). The median sacral artery is about 2.3 mm wide at the coccyx (Tribus and Belanger,2001; Guvencer et al,2009). The coccygeal region is also supplied by a sizeable coccygeal branch from the inferior gluteal artery which is given off behind the sacrospinous ligament and passes posteriorly to perforate the sacrotuberous ligament at multiple sites before terminating in gluteus maximus (Thompson et al,1999).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the aim of this study was to describe the embryonic coccygeal body with the assumed contribution of nerves. Although the name “median sacral artery” has often been replaced by “middle sacral artery” due to the rather rare midline course in adults (Güvencer et al, ), the former or original name is used in the present embryonic study.…”
Section: Introductionmentioning
confidence: 99%